Multimorbidity and patterns of chronic conditions in a primary care population in Switzerland: a cross-sectional study. Issue 6 (2nd July 2017) - Déruaz-Luyet, Anouk; N'Goran, A Alexandra; Senn, Nicolas; Bodenmann, Patrick; Pasquier, Jérôme; Widmer, Daniel; Tandjung, Ryan; Rosemann, Thomas; Frey, Peter; Streit, Sven; Zeller, Andreas; Haller, Dagmar M; et al.
Abstract : Objective: To characterise in details a random sample of multimorbid patients in Switzerland and to evaluate the clustering of chronic conditions in that sample. Methods: 100 general practitioners (GPs) each enrolled 10 randomly selected multimorbid patients aged ≥18 years old and suffering from at least three chronic conditions. The prevalence of 75 separate chronic conditions from the International Classification of Primary Care-2 (ICPC-2) was evaluated in these patients. Clusters of chronic conditions were studied in parallel. Results: The final database included 888 patients. Mean (SD) patient age was 73.0 (12.0) years old. They suffered from 5.5 (2.2) chronic conditions and were prescribed 7.7 (3.5) drugs; 25.7% suffered from depression. Psychological conditions were more prevalent among younger individuals (≤66 years old). Cluster analysis of chronic conditions with a prevalence ≥5% in the sample revealed four main groups of conditions: (1) cardiovascular risk factors and conditions, (2) general age-related and metabolic conditions, (3) tobacco and alcohol dependencies, and (4) pain, musculoskeletal and psychological conditions. Conclusion: Given the emerging epidemic of multimorbidity in industrialised countries, accurately depicting the multiple expressions of multimorbidity in family practices' patients is a high priority. Indeed, even in a setting where patients have direct access to medical specialists, GPs nevertheless retain a key role as coordinators and often as the sole medical reference for multimorbid patients.